From Leadership to Citizenship Behavior in Public Organizations: When Values Matter. (June 2014) - Ritz, Adrian; Giauque, David; Varone, Frédéric; Anderfuhren-Biget, Simon
After decades of management reforms in the public sector, questions on the impact of leadership behavior in public organizations have been attracting increasing attention. This article investigates the relationship between transformational leadership behavior and organizational citizenship behavior as one major extra-role outcome of transformational leadership. Referring to a growing body of research that shows the importance of public service values and employee identification in public administration research, we include public service motivation and organizational goal clarification as mediating variables in our analysis. Structural equation modeling is applied as the method of analysis for a sample of 569 public managers at the local level of Switzerland. The findings of our study support the assumed indirect relationship between leadership and employee behavior and emphasize the relevance of public service values when analyzing leadership behavior in public sector organizations.